Aseptic meningitis following therapy with immune globulins: a combination of product features and patient characteristics?. Issue 12 (2nd November 2016) - Berg, Roger; Fuellenhals, Elisabeth
Abstract : BACKGROUND: Aseptic meningitis (AM) represents a recognized side effect of immune globulin (IG) therapy and may warrant additional diagnostic procedures and therapy with anti‐infective drugs until a definite diagnosis can be established. Although, to date, only small case series have been published, the objective of the current study was to investigate a large case series of patients with AM. STUDY DESIGN AND METHODS: The pharmacovigilance safety database of a 10% liquid IG (Gammagard Liquid) was queried for all reports of AM. Patient demographics, treatment‐specific data, and product‐specific data were determined. The proportional reporting rates of AM were compared according to the route of administration (intravenous vs. subcutaneous) and molecular size distribution of IG lot (dimer content ≥ 8 vs. < 8%). RESULTS: In total, 144 AM episodes were reported in 136 distinct patients. Females were affected by AM nearly four times more than males. AM was not limited to patients who received high‐dose IG therapies but was observed in those who received low‐dose regimens in percentages comparable to the estimated usage patterns of IG. Lots that had high dimer values were associated with AM significantly more often than lots that had low dimer values (p < 0.001), and subcutaneous IG administration was associated with lower rates of AM compared with intravenous IG administration (p = 0.055). CONCLUSION: In contrast to previously published data, AM was observed in both low‐dose and high‐dose regimens without favoring high IG doses, and females were affected nearly four times more often than males. Immunoglobulin G dimers may play a role in the etiology of AM, and subcutaneous administration may be associated with a lower rate of AM compared with intravenous administration.